Hubungan Sistem Seleksi Masuk Perguruan Tinggi dengan Indeks Prestasi Kumulatif Lulusan Sarjana Kedokteran - Tulle, Yoan Melani Efelian; Ratu, Kristian; Sagita, Sidarta; Lidia, Kartini (Cendana Medical Journal, 2023)
Background: The Grade Point Average (GPA) is an essential factor in medical education, since it is used to evaluate the quality of graduates, with a correlation between a higher GPA and higher-quality doctors. College admission selection system, which is aimed at identifying prospective students who are most likely to succeed in completing education at Faculty of Medicine and has Predictive Validity for undergraduate GPA, is one of factors that can influence GPA.Objective: Knowing the connection between college admissions selection system and grade point average for medical graduates.Methods: This research is an analytic observational study using a Cross Sectional design conducting to utilize a questionnaire on medical graduates for 2020 and 2021 periods. Total Sampling was utilized with a total sample size of 125 people (57 medical graduates for 2020 period and 68 medical graduates for 2021 period) who matched the research criteria. The research was evaluated univariately and bivariately using Somers'd correlation and One Way ANOVA tests, respectively.Result: The bivariate analysis for medical graduates for 2020 period produced a p value = 0.349. For medical graduates, a value p = 0.001 and r = 0.280 were obtained for 2021 period. The value of p = 0.010 was achieved in the One Way ANOVA test.Conclusion: For 2020 period, there is no relationship to college admission selection system and GPA of medical graduates. However, for 2021 period, there is a significant relationship between college admission selection system and GPA of medical graduates, and relationship is included in a weakly positive correlation. In addition, the average GPA of medical graduates varies according on college admission selection system. Graduates who enter tertiary institutions by SNMPTN route have the highest average GPA, followed by those who enter through SBMPTN and SMMU.Keywords: College Admissions Selection System, GPA, Medical Graduate Graduates